Soft-sediment deformation structures in cores from lacustrine slurry deposits of the Late Triassic Yanchang Fm. (central China) - Yang, Renchao; Loon, A.J. (Tom) van; Yin, Wei; Fan, Aiping; Han, Zuozhen (Geologos, 2016)
The flows and the resulting SSDS were probably triggered by earthquakes, volcanic eruptions, shear stress of gravity flows, and/or the sudden release of overburden-induced excess pore-fluid pressure. The tectonically active setting, the depositional slope and the high sedimentation rate facilitated the development of soft-sediment deformations, which consist mainly of load casts and associated structures such as pseudonodules and flame structures. Sediments with such deformations were occasionally eroded by slurries and became embedded in their deposits.